Giant Cell Lesions of the Jaws Involving RASopathy Syndromes - Melissa Luna; Nicholas Wolsefer; Carlos-Xavier Zambrano; Ivan James Stojanov (University of Zagreb. School of Dental Medicine, 2022)
Objective: Giant cell lesions of the jaws (GCLJ) may rarely occur in the setting of RASopathy syndromes such as Noonan syndrome or neurofibromatosis I. Recently, central giant cell granulomas (CGCG), the most common of the GCLJ, have been recognized as benign neoplasms characterized by Ras/MAPK signaling pathway mutations. This provides a rational basis for understanding GCLJ in RASopathy syndromes as syndromically occurring CGCG. This review aims to summarize the clinico-pathologic features of syndromic CGCG and to review the salient clinical and craniofacial features of the syndromes in which they may rarely occur. Material and Methods: An electronic search in 3 data-bases was performed, looking for GCLJ/CGCG in RASopathy syndromes. Results: 124 CGCG in 56 patients were identified across 6 RASopathy syndromes. Median age at syndromic CGCG diagnosis is 11 years; 69.6% (39/56) patients developed two or more CGCG; 58.9% (33/56) presented with bilateral posterior mandibular CGCGs, mimicking cherubism. Of 88 CGCG with follow-up, 22.4% (13/58) of excised/resected CGCG recurred while 46.7% (14/30) of monitored CGCG showed continued growth. Conclusion: Syndromic CGCG involves multiple RASopathy syndromes and may mimic cherubism or, when solitary, sporadically occurring CGCG. Familiarity with other clinical findings of RASopathy syndromes is critical for appropriate diagnosis and patient management.